The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijerph17145213
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Air Quality in a Subway Station with Fully Enclosed Platform Screen Doors

Abstract: In this study, the indoor air quality (IAQ) was investigated in a subway station with fully enclosed platform screen doors in Beijing, China. Eight indoor air pollutants, including PM2.5, PM10, SO2 (sulfur dioxide), NO2 (nitrogen dioxide), NH3 (ammonia), CO (carbon monoxide), CH2O (formaldehyde) and TVOC (total volatile organic compound), were measured for six consecutive days in October 2019. The results indicated that the IAQ in the subway station was basically stable at good levels for most times during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Computational modeling methods are widely used to predict the processes of dusty air flow movement [22][23][24][25], which make it possible to determine the parameters of dust transfer processes and the effectiveness of dust collection methods and perform air quality assessment in buildings and structures [26,27]. In general, it is possible to note the high interest of scientists around the world in studies of the dustiness of air in subways [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]28] and methods of reducing dust concentrations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Computational modeling methods are widely used to predict the processes of dusty air flow movement [22][23][24][25], which make it possible to determine the parameters of dust transfer processes and the effectiveness of dust collection methods and perform air quality assessment in buildings and structures [26,27]. In general, it is possible to note the high interest of scientists around the world in studies of the dustiness of air in subways [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]28] and methods of reducing dust concentrations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A lot of research has already studied the presence of PM2.5 and PM10 in subway stations [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] ]. The geographical locations covered by this research are shown in Table 1 .…”
Section: Introductionmentioning
confidence: 99%